LIMITES ADMINISTRATIVES ET CONFLITS DANS LA PROVINCE DU HAUT-UELE EN REPUBLIQUE DEMOCRATIQUE DU CONGO - ATUBA, Jules MAGBAY (IJRDO - Journal of Social Science and Humanities Research, 2021)
The present article aims at presenting the conflicts related to the administrative boundaries of the territorial entities in Upper-Uele(Haut-Uele) province by portraying the outline of limologic theory. Those different bordering conflicts will also be examined in all the six territories of the province under investigation(Haut-Uele) by displaying the causes and manifestation of those conflicts.